Radiopacity of restorative materials using digital images - Salzedas, Leda Maria Pescinini [UNESP]; Louzada, Mário Jefferson Quirino [UNESP]; De Oliveira Filho, Antonio Braz [UNESP] (FapUNIFESP (SciELO), 2006)
The radiopacity of esthetic restorative materials has been established as an important requirement, improving the radiographic diagnosis. The aim of this study was to evaluate the radiopacity of six restorative materials using a direct digital image system, comparing them to the dental tissues (enamel-dentin), expressed as equivalent thickness of aluminum (millimeters of aluminum). Five specimens of each material were made. Three 2-mm thick longitudinal sections were cut from an intact extracted permanent molar tooth (including enamel and dentin). An aluminum step wedge with 9 steps was used. The samples of different materials were placed on a phosphor plate together with a tooth section, aluminum step wedge and metal code letter, and were exposed using a dental x-ray unit. Five measurements of radiographic density were obtained from each image of each item assessed (restorative material, enamel, dentin, each step of the aluminum step wedge) and the mean of these values was calculated. Radiopacity values were subsequently calculated as equivalents of aluminum thickness. Analysis of variance (ANOVA) indicated significant differences in radiopacity values among the materials (P<0.0001). The radiopacity values of the restorative materials evaluated were, in decreasing order: TPH, F2000, Synergy, Prisma Flow, Degufill, Luxat. Only Luxat had significantly lower radiopacity values than dentin. One material (Degufill) had similar radiopacity values to enamel and four (TPH, F2000, Synergy and Prisma Flow) had significantly higher radiopacity values than enamel. In conclusion, to assess the adequacy of posterior composite restorations it is important that the restorative material to be used has enough radiopacity, in order to be easily distinguished from the tooth structure in the radiographic image. Knowledge on the radiopacity of different materials helps professionals to select the most suitable material, along with other properties such as biocompatibility, adhesion and esthetic.
Keywords: Densitometry; Dental material; Digital radiography